2022
DOI: 10.1038/s44161-022-00157-y
|View full text |Cite
|
Sign up to set email alerts
|

Rad regulation of CaV1.2 channels controls cardiac fight-or-flight response

Abstract: Fight-or-flight responses involve β-adrenergic-induced increases in heart rate and contractile force. In the present study, we uncover the primary mechanism underlying the heart’s innate contractile reserve. We show that four protein kinase A (PKA)-phosphorylated residues in Rad, a calcium channel inhibitor, are crucial for controlling basal calcium current and essential for β-adrenergic augmentation of calcium influx in cardiomyocytes. Even with intact PKA signaling to other proteins modulating calcium handli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 63 publications
2
20
0
Order By: Relevance
“…Emission was detected at 510 nm through a Nikon Fluor ×10 objective by a Prime BSI-Express sCMOS (scientific Complementary Metal–Oxide–Semiconductor) camera (Teledyne Photometrics) and Nikon Elements (Version 5.21) as previously described. 57 Cells were randomly selected for rhythmicity analysis. Calcium fluorescence was analyzed using a written Python code available on Github.…”
Section: Methodsmentioning
confidence: 99%
“…Emission was detected at 510 nm through a Nikon Fluor ×10 objective by a Prime BSI-Express sCMOS (scientific Complementary Metal–Oxide–Semiconductor) camera (Teledyne Photometrics) and Nikon Elements (Version 5.21) as previously described. 57 Cells were randomly selected for rhythmicity analysis. Calcium fluorescence was analyzed using a written Python code available on Github.…”
Section: Methodsmentioning
confidence: 99%
“…On closer inspection, the L-type calcium channel inhibitor Rrad was identified as one of the most significantly upregulated genes at 1 hour (Fc:4.91, FDR:3.2e-8) and 3 hours (Fc:4.51, FDR:9.2e-9) post rmIL11 treatment [Fig2A, B]. The Rrad protein product RAD-GTPase is a well-characterised and potent inhibitor of calcium current through L-type calcium channels 24,25 and its acute upregulation may account for the changes in calcium transients seen in isolated CM preparations.…”
Section: Resultsmentioning
confidence: 99%
“…Its pharmacological blockade was observed to reduce the rate of activation of sinoatrial cells [126][127][128]. The channels carrying the current were long thought to be phosphorylated directly by PKA, but recent studies demonstrated that the cAMP-dependent activation of the current is in fact mediated by Rad, a channel inhibitor associated with the local signalosome [129][130][131]. The regulatory sequence therefore involves cAMP activation of PKA, phosphorylation of Rad molecules in the vicinity and consequent release of its inhibitory action on L-type calcium current, which is enhanced.…”
Section: Camp and Membrane Clockmentioning
confidence: 99%